2020
DOI: 10.3390/su12166473
|View full text |Cite
|
Sign up to set email alerts
|

“Work and Surroundings”: A Training to Enhance Career Curiosity, Self-Efficacy, and the Perception of Work and Decent Work in Adolescents

Abstract: The development of professional identity starts with childhood. In adolescence, individuals should have appropriate resources to make choices; high levels of self-efficacy and professional curiosity, as well as better representations of the concept of work and decent work, could support adolescents in their planning of the future. For this reason, we developed a training aimed at providing adolescents with resources of professional curiosity and self-efficacy, which would also increase their representation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…In other studies, we have shown that career education and counseling can do a lot in this direction even starting from adolescence, helping young people to have broad ideas of work and decent work, as well as promoting dimensions, such as career adaptability and self-efficacy (Zammitti et al, 2020) or hope and optimism (Santisi et al, 2021). Furthermore, the study offers a contribution to broadening the field of career education using mixed techniques (Blustein et al, 2005;Schultheiss, 2005;Whiston and Rahardja, 2005).…”
Section: Conclusion and Limitationsmentioning
confidence: 91%
See 3 more Smart Citations
“…In other studies, we have shown that career education and counseling can do a lot in this direction even starting from adolescence, helping young people to have broad ideas of work and decent work, as well as promoting dimensions, such as career adaptability and self-efficacy (Zammitti et al, 2020) or hope and optimism (Santisi et al, 2021). Furthermore, the study offers a contribution to broadening the field of career education using mixed techniques (Blustein et al, 2005;Schultheiss, 2005;Whiston and Rahardja, 2005).…”
Section: Conclusion and Limitationsmentioning
confidence: 91%
“…To investigate the representation of work and decent work, as suggested by other studies (Ferrari et al, 2009 ; Zammitti et al, 2020 ; Magnano et al, 2021b ), we used two open questions: what is your definition of work? What is your definition of decent work?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in the context of the changing nature of the 21st-century world of work, considering that mental and physical health costs of job insecurity could be high [ 142 ] and that daily value-based actions are related to greater daily psychological well-being and lower daily psychological distress [ 143 ], it is important to include the exploration of one’s personal values within educational and professional guidance programs that aim to promote risk intelligence as a useful resource for career adaptability and career development. Indeed, career counsellors should be concerned with the promotion of personal resources in different contexts and educational levels [ 144 , 145 , 146 ]. Clarity about personal values is a core dimension of psychological flexibility [ 63 ] and, therefore, can support effective actions in the direction of what people want to achieve, helping them to move in contexts of uncertainty.…”
Section: Implications For Future Studies and Practicementioning
confidence: 99%